Roll-to-roll slot-die coated P–I–N perovskite solar cells using acetonitrile based single step perovskite solvent system. Issue 7 (14th May 2020) - Burkitt, Daniel; Patidar, Rahul; Greenwood, Peter; Hooper, Katherine; McGettrick, James; Dimitrov, Stoichko; Colombo, Matteo; Stoichkov, Vasil; Richards, David; Beynon, David; Davies, Matthew; Watson, Trystan
Abstract : Roll-to-roll coating of all active layers is demonstrated for a P–I–N perovskite solar cell stack, using a single step perovskite ink with an acetonitrile solvent system and flexible plastic substrate. Abstract : Roll-to-roll coating of all active layers is demonstrated for a P–I–N perovskite solar cell stack, using a single step perovskite ink with an acetonitrile solvent system and flexible plastic substrate. A slot-die coating roll-to-roll process (with a common coating speed for all layers) is developed by using appropriate length meniscus guides as part of the coating head for each ink rheology. High performance devices are demonstrated with four roll-to-roll slot-die coated layers and evaporated top electrode. The drying conditions of the perovskite layer are optimized and found to be critical to achieving good performance. Multi solvent blend systems for the electron collection layer are developed that are more industrially compatible than the commonly used chlorobenzene solvent system and make use of a gradient of solvent volatilities to give both good macro film formation and rapid drying. A stabilised power conversion efficiency of 12.2% is demonstrated, that is the highest reported to date for devices with all layers other than the top electrode deposited roll-to-roll. This work demonstrates the feasibility of a roll-to-roll fabrication process for perovskite solar cells that could be transferred to a fully inline roll-to-roll process with all coating and drying stages made sequentially on one line running at a common coating speed and further demonstrates the potential to produce high efficiency photovoltaics using roll-to-roll fabrication methods.